Analisis Dampak Lingkungan Emisi Gas Rumah Kaca Menggunakan Metode Life Cycle Assessment di Perusahaan Penyedia Layanan dan Perakitan Sistem Turbocharger - Suhada, Aisyah Ramadhanti; Murti, Restu Hikmah Ayu; Rachmanto, Tuhu Agung; Wibisana, Hendrata; Rosariawari, Firra (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Greenhouse gas (GHG) emissions from the industrial sector have a significant impact on global climate change. To assess the overall environmental impact, an analysis capable of mapping emissions from various operational activities is required. This study aims to analyze GHG emissions in a manufacturing company that focuses on turbocharger system assembly and services using the Life Cycle Assessment (LCA) method. The analysis was conducted with reference to the 2006 IPCC Guidelines and openLCA software, with the scope of research covering the transportation and energy sectors within the company. The inventory results show that the energy sector is the main contributor to emissions, with the largest impact category being climate change (GWP 100a). Next, a scenario analysis was conducted, namely real conditions, the use of solar panels, the use of diesel fuel, and a mixture. A comparison of the scenarios showed that the use of renewable energy in the form of solar panels could significantly reduce GHG emissions compared to the current conditions. This study confirms that the application of LCA can provide a quantitative picture of the potential environmental impact and serve as a scientific basis for formulating GHG emission management strategies in the industrial sector.